How to fight SARS-COV-2 vaccine hesitancy in patients suffering from chronic and immune-mediated skin disease: four general rules - A. Campanati; E. Martina; F. Diotallevi; G. Radi; G. Kontochristopoulos; D. Rigopoulos; S. Gregoriou; A. Offidani (Taylor & Francis Group, 2021)
All public health ministries have implemented strategies to contain the spread of COVID-19 worldwide. Vaccines against SARS-CoV-2 still represent the most effective weapon to combat the circulation of the virus, in order to decrease the impact of COVID-19 on the general health of the population, to prevent the emergence of new SARS-CoV-2 variants and avoid excessive hospitalization. However, the success of a vaccination campaign largely depends on the penetrance of the message addressed to general population, which takes on an even more strategic value when vaccine candidates suffer from chronic diseases. In this view, patients suffering from immune-mediated skin diseases could represent a "weak link in the vaccine chain." Our main objective is to focus attention on four main elements in support of vaccination strategy in order to promote the patients' awareness to be at highest risk of negative consequences in case of SARS-Cov-2 infection, and to build, strengthen and maintain trust in vaccines' efficacy and safety.